Nilai Mitsaqan Ghalizha melalui Program Tepuk Sakinah dalam Menjawab Tantangan Perkawinan Era Digital - Widia Usada; Heri Firmansyah (ALSYS, 2026)
Marriage in Islam is understood as mitsaqan ghalizha, namely a great and firm covenant that contains five fundamental values, including zawaj, mitsaqan ghalizhan, mu’asyarah bil ma’ruf, musyawarah, and taradhin. In the digital era, these values face serious challenges due to the spread of phubbing, cyber-infidelity, text-based miscommunication, and the tendency to compare domestic life through social media. This study aims to normatively analyze the values of mitsaqan ghalizha contained in the Tepuk Sakinah program and to examine its relevance as an instrument for strengthening family resilience in facing the challenges of marriage in the digital era. This study used a normative legal method (library research) with a conceptual approach and Islamic family jurisprudence analysis. The results show that the lyrics and structure of Tepuk Sakinah are normatively aligned with the principles of Islamic family law and represent the values of zawaj, mitsaqan ghalizhan, mu’asyarah bil ma’ruf, musyawarah, and taradhin in a simple and memorable form of education. This program can also be understood as a manifestation of Sadd Adz-Dzari’ah and Maslahah Mursalah in the context of contemporary jurisprudence because it has the potential to serve as a preventive instrument for mitigating family conflict in the digital era. The conclusion of this study affirms that Tepuk Sakinah is an educational innovation in marriage guidance that is relevant for adaptively strengthening Muslim family resilience. The implications of this study indicate that the program not only strengthens prospective brides’ and grooms’ understanding of the sacred values of marriage but can also function as a practical guide in countering the destructive impact of technology on family relations.